2002
DOI: 10.1080/10409230290771519
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Consumption of Probiotics and Prebiotics on Serum Lipid Levels in Humans

Abstract: The objective of this article is to review existing studies concerning the effects of probiotics and prebiotics on serum cholesterol concentrations, with particular attention on the possible mechanisms of their action. Although not without exception, results from animal and human studies suggest a moderate cholesterol-lowering action of dairy products fermented with appropriate strain(s) of lactic acid bacteria and bifidobacteria. Mechanistically, probiotic bacteria ferment food-derived indigestible carbohydra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
211
0
16

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 391 publications
(235 citation statements)
references
References 63 publications
8
211
0
16
Order By: Relevance
“…Probiotic bacteria are able to ferment dietary fibres to produce short-chain fatty acids in the gut that may result in a decrease in the systemic levels of blood lipids by inhibiting hepatic cholesterol synthesis (Pereira and Gibson, 2002). Although the yoghurt contained two probiotic cultures, no significant change in the concentration and ratio of shortchain fatty acids in faeces were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Probiotic bacteria are able to ferment dietary fibres to produce short-chain fatty acids in the gut that may result in a decrease in the systemic levels of blood lipids by inhibiting hepatic cholesterol synthesis (Pereira and Gibson, 2002). Although the yoghurt contained two probiotic cultures, no significant change in the concentration and ratio of shortchain fatty acids in faeces were observed.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the ability of particular strain of probiotic bacteria to attach permanently to the gut wall and hence continuous supply might be necessary to exert the effects. 21,22 The results of our previous study indicated that these bacteria are not able to colonize the intestine and are quickly eliminated in feces. 9 As such, daily consumption of probiotic products is necessary for any longterm effect on metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol is used to synthesize new bile acids in a homeostatic response, resulting in lowering of serum cholesterol. [19][20][21] Ooi and Liong 20 in a review article attributed these controversial findings to various factors such as different strains of probiotics, administration dosage, analytical accuracy of lipid analyses, duration of treatment period, clinical characteristic of subjects, inadequate sample sizes, and lack of suitable controls or placebo groups. 2 Considering the mentioned reasons hypothesized by Ooi and Liong, 20 normolipidemic condition of used rat model in the current study may be a reason for failure of these probiotic bacteria in changing lipid profile.…”
Section: Discussionmentioning
confidence: 99%
“…26 It has been previously postulated that some probiotic lipid-lowering clinical trials lack appropriate strain selection, method of delivery or clinical design. 31 For the current study, a systematic approach was applied, including identifying a strain, L. reuteri NCIMB 30242, with the appropriate phenotypic characteristics including elevated natural BSH expression, ensuring the safety of the strain through phenotypic and genotypic characterization 32 and optimizing the production parameters of the strain.…”
Section: Weekmentioning
confidence: 99%